Empire of the Bay an illustrated history of the Hudson's Bay Company - Newman, Peter C. (Madison Press Books, 1989)
Popular history of the Hudson's Bay Company in Canada, including the fur trade, exploration, native peoples, social history, northern trading posts and a chronology.
Keywords: Compagnie de la Baie d'Hudson - Histoire; Compagnie de la Baie d'Hudson - Histoire - Ouvrages illustrés; Hudson's Bay Company -- History; Hudson's Bay Company; Fourrures - Commerce - Canada - Histoire; Fourrures - Commerce - Histoire - Ouvrages illustrés; Geschichte; Fur trade -- Canada -- History; Nord-Ouest canadien - Histoire - 1870-1905; Nord-Ouest canadien - Histoire - 1870-1905 - Ouvrages illustrés; Nord-Ouest canadien - Histoire - Jusqu'à 1870; Nord-Ouest canadien - Histoire - Jusqu'à 1870 - Ouvrages illustrés; Kanada; Northwest, Canadian -- History -- 1870-1905; Northwest, Canadian -- History -- 1870-1905 -- Pictorial works; Northwest, Canadian -- History -- To 1870; Northwest, Canadian -- History -- To 1870 -- Pictorial works; Bildband